Pengaruh Pemberian Campuran Fermentasi Ampas Tahu dan Dedak Padi Dalam Ransum Terhadap Performa Bebek Hibrida - Lindidjawa, Simon Kalikit; Hambakodu, Marselinus; Kiha, Amelia Florida (JURNAL PETERNAKAN SABANA, 2024)
This study aims to determine the effect of giving a mixture of fermented tofu pulp and rice bran in rations on the performance of hybrid ducks. This research was carried out in Lambanapu Village, Kambera District, East Sumba Regency which took place from November to December 2023, where there was a 2-week adaptation period and 8 weeks of data collection period. This study used an experimental method with a Complete Random Design (RAL) with 4 treatments and 4 replicates, namely P0:BR2 (basal feed), P1: BR2 80% + tofu pulp fermentation 10% + rice bran fermentation 10%, P2: BR2 60% + tofu pulp fermentation 20% + rice bran fermentation 20%, and P3: BR2 40% + tofu pulp fermentation 30% + rice bran fermentation 30%. The results of this study showed that the administration of tofu pulp and fermented rice bran had a real effect (P<0.05) on ration consumption and ration conversion, but had no effect on body weight gain. In conclusion, the application of 40% BR2 and a mixture of fermented tofu pulp 30% and rice bran 30% in the ration can increase ration consumption, but produce a high conversion value and the same body weight gain in Hybrid ducks.